Hubungan Tingkat Kepatuhan Minum Obat Pasien Tuberkulosis Terhadap Efek Samping Obat Anti Tuberkulosis (OAT) - Berly Afilla Christy; Ressi Susanti; Nurmainah Nurmainah (Journal Syifa Sciences and Clinical Research, 2022)
One of the causes of failure in tuberculosis treatment therapy is the incidence of side effects of anti-tuberculosis drugs (OAT) which can affect drug adherence in tuberculosis patients. The purpose of this study was to evaluate the relationship of OAT side effects to patient medication adherence at the Sungai Betung Public Health Center, Bengkayang Regency. The method in this research is an observational study with a cross sectional study design . The study design was a non-experimental epidemiological study. Data was collected by collecting medical record data and questionnaires containing 11 questions related to OAT side effects and drug compliance. The results showed the characteristics of the majority of patients of productive age as much as 71.42%, male sex of 82.85% and the average being undergoing a category 1 treatment regimen. Distribution of OAT side effects, as many as 51.43% of patients responded well to side effects. OAT and the remaining 48.57% of patients did not respond well to OAT side effects, while the distribution of patient compliance in taking drugs was 65.71% of patients had high adherence and 34.29% of patients had low adherence. The results of statistical tests to determine the relationship between OAT side effects on adherence using the Chi-square test showed p value0.05 (p value= 0.024) then Ho was accepted. The conclusion is that there is a significant relationship between OAT side effects and adherence to medication for pulmonary tuberculosis patients at the Sungai Betung Public Health Center, Bengkayang Regency.